The Analysis of Kandoushi to Express the Emotions of Wonder and Shock in Jujutsu Kaisen Manga Volume 21-25 by Gege Akutami - Setiawan, Haris; Dewandono, Wiranto Aji (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to understand the use of kandoushi to express feelings of surprise and shock in Jujutsu Kaisen manga volumes 21-25. The method used was descriptive qualitative, which involved analyzing 59 data findings, of which 11 data were taken for further analysis. The results showed that kandoushi expressing surprise (odoroki) consists of kandoushi such as ああ(aa), あ(a), え(e), お(o), and なっ(natt) or なに(nani), while the kandoushi that express the feeling of surprise (yosougai no odoroki or igaikan) include は(ha), はあ(haa), ええ(ee), へえ(hee), あれ(are), and なんと(nanto). The use of these kandoushi in speech is often accompanied by emotions such as confusion and others, influenced by the discourse context, build the meaning of the speaker's speech. These findings illustrate the importance of further analyzing the use of kandoushi in interaction and discourse, both in spoken and written language, to understand the nuances of emotion and meaning that speakers want to convey.